Pengaruh Kinerja Agen Asuransi terhadap Kepuasan Nasabah dalam Proses Penyelesaian Klaim Produk Asuransi Jiwa: Studi Kasuspada AJB Bumiputera 1912 Wilayah Medan - Ramadhani, Devi; Soemitra, Andri; Imsar (Ikatan Da'i Indonesia, 2023)
This research aims to determine whether or not there is an influence of agent performance consisting of quality, quantity and agent effectiveness on customer satisfaction at the AJB Bumiputera 1912 Medan Region company. This research uses three independent variables, namely quality, quantity and effectiveness with one dependent variable, namely customer satisfaction. The methodology used in this research is a quantitative method and an associative approach. Samples were taken from AJB Bumiputera 1912 customers in the Medan area, totaling 95 people. The type of data used is primary data. The data analysis method used is Instrument Test, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. Based on the results of the T test, the agent quality variable has a positive and significant effect on customer satisfaction, the quantity variable shows that this variable has a significant effect on customer satisfaction, and the agent effectiveness variable also has a positive and significant effect on customer satisfaction. Based on the results of the F-test analysis, it was found that the variables of quality, quantity and agent effectiveness together have a positive and significant influence on customer satisfaction. Based on the results of the R Square value obtained using SPSS valued at 0.552, which means that it explains the magnitude of the influence of quality, quantity and agent effectiveness variables together on customer satisfaction worth 55.2% and the remaining 44.8% can be explained by other variables not included in Research Model.